2016
DOI: 10.1038/srep34791
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Configuration Modulates Mechanically Induced Changes in Mesenchymal Stem Cell Osteogenesis, Morphology, and Stiffness

Abstract: Mesenchymal stem cells (MSC) responding to mechanical cues generated by physical activity is critical for skeletal development and remodeling. Here, we utilized low intensity vibrations (LIV) as a physiologically relevant mechanical signal and hypothesized that the confined cytoskeletal configuration imposed by 2D culture will enable human bone marrow MSCs (hBMSC) to respond more robustly when LIV is applied in-plane (horizontal-LIV) rather than out-of-plane (vertical-LIV). All LIV signals enhanced hBMSC proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
5
45
0
Order By: Relevance
“…The HF vibration has been especially popular in inducing the osteogenic responses of stem cells [9][10][11]35] and in differentiation of the vocal fold tissues [16]. However, these stimulation effects have been studied with methods, which require special treatments of the samples and don't allow live cell imaging.…”
Section: Applicability For Mechanobiology Research With Live Cellsmentioning
confidence: 99%
“…The HF vibration has been especially popular in inducing the osteogenic responses of stem cells [9][10][11]35] and in differentiation of the vocal fold tissues [16]. However, these stimulation effects have been studied with methods, which require special treatments of the samples and don't allow live cell imaging.…”
Section: Applicability For Mechanobiology Research With Live Cellsmentioning
confidence: 99%
“…Flow shear stress (FSS) can also induce a variety of responses such as recruitment, proliferation, and osteogenic differentiation of BMSCs, thus promoting bone formation . Low intensity vibrations signal enhanced BMSC proliferation, osteogenic differentiation, and up‐regulation of genes associated with cytoskeletal structure . These responses to mechanical stimuli are reduced with aging, and the age‐related loss of osteogenic potential in BMSCs can be attributed in part to the impairment in IGF‐1 signaling in BMSCs.…”
Section: Role Of Igf‐1 In the Mesenchymal Stem Cell Response To Mechamentioning
confidence: 99%
“…23 Low intensity vibrations signal enhanced BMSC proliferation, osteogenic differentiation, and up-regulation of genes associated with cytoskeletal structure. 24 These responses to mechanical stimuli are reduced with aging, and the age-related loss of osteogenic potential in BMSCs can be attributed in part to the impairment in IGF-1 signaling in BMSCs. On the other hand IGF-1 overexpression in aging BMSCs facilitates the formation of cell clusters in scaffolds, increases cell survival inside the cell clusters, induces the expression of osteoblast markers, and enhances the biomineralization of cell clusters.…”
mentioning
confidence: 99%
“…Exogenous application of small magnitude mechanical regimes in the form of low intensity vibrations (LIV) ranging between 0.1-2g acceleration magnitudes and 20-200Hz frequencies were shown to be effective in improving bone and muscle indices in clinical and preclinical studies 17 . At the cellular level, our group has reported that application of LIV increases MSC contractility 18 , activates RhoA signaling 19 , and results in increased osteogenic differentiation and proliferation of MSCs 20 .…”
Section: Introductionmentioning
confidence: 99%